The human homolog T of the mouse T(Brachyury) gene; gene structure, cDNA sequence, and assignment to chromosome 6q27. - Edwards, Y H; Putt, W; Lekoape, K M; Stott, D; Fox, M; Hopkinson, D A; Sowden, J

(untitled) (Genome Research, 1996)
We have cloned the human gene encoding the transcription factor T. T protein is vital for the formation of posterior mesoderm and axial development in all vertebrates. Brachyury mutant mice, which lack T protein, die in utero with abnormal notochord, posterior somites, and allantois. We have identified human T genomic clones and derived the mRNA sequence and gene structure. There is 91% amino acid identity between human and mouse T proteins overall and complete identity across 77 amino acids of the T-box motif within the DNA-binding domain. Human T expression is very similar to that found for T in other vertebrate species and is confined to cells derived from the notochord. The human T gene maps to chromosome 6q27 and is only the second human member of the T-box gene family to be described.